2007
DOI: 10.1136/emj.2006.038695
|View full text |Cite
|
Sign up to set email alerts
|

A randomised, double-blind, placebo-controlled study to evaluate the role of formoterol in the management of acute asthma

Abstract: Aim: To evaluate the efficacy and tolerability of formoterol delivered by Aerolizer in the emergency department. Methods: A single-centre, double-blind, randomised, placebo-controlled, parallel group study was conducted in patients seeking emergent care for an acute exacerbation of asthma. Patients were randomly assigned to one of two groups: group 1 (salbutamol), receiving a total dose of 600 mg salbutamol (200+200+200) delivered by a meter-dose inhaler into a spacer device as two puffs at 20 min intervals; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…43 Appetite suppressants act by central mechanisms involving alpha-adrenoceptors, while indirectly cause secretion of protein by releasing noradrenaline from glandular nerve terminals. 44 Decongestants 45 and beta 2-agonists bronchodilators 46 are sympathomimetics drugs that also are associated with salivary dysfunction.…”
Section: Drugsmentioning
confidence: 99%
“…43 Appetite suppressants act by central mechanisms involving alpha-adrenoceptors, while indirectly cause secretion of protein by releasing noradrenaline from glandular nerve terminals. 44 Decongestants 45 and beta 2-agonists bronchodilators 46 are sympathomimetics drugs that also are associated with salivary dysfunction.…”
Section: Drugsmentioning
confidence: 99%
“…Dryness of mouth was the most reported side effect of formoterol inhalation in one study. 15 In our study, the greatest number of AEs were reported in the system organ class of central nervous system disorders, with headache and muscle tremors being the most commonly reported. In few studies, the impact of high-dose formoterol on heart rate, blood pressure, serum potassium, electrocardiogram changes, and arterial blood gas were assessed which showed identical changes comparable with salbutamol.…”
Section: Discussionmentioning
confidence: 52%
“…Several studies have shown the efficacy of formoterol in acute non-severe asthma, acute severe asthma, exercise induced bronchospasm, childhood asthma, and COPD. [15][16][17][18][19] Although few studies have shown clinically significant improvement in lung function (FEV1) with formoterol when compared with salbutamol, 16 most studies have shown a comparable efficacy. 15,17 Safety of formoterol is also well documented even at high doses in patients with asthma and COPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13–17] Most of the studies have used formoterol with terbuhaler,[814] aerolizer,[13] or metered dose inhaler. [1718] However, studies using formoterol nebulization are lacking.…”
Section: Discussionmentioning
confidence: 99%